Composition operators from the Bloch space into the spaces QT - Pengcheng Wu; Hasi Wulan (International Journal of Mathematics and Mathematical Sciences)
Suppose that φ(z) is an analytic self-map of the unit disk Δ. We consider the boundedness of the composition operator Cφ from Bloch space ℬ into the spaces QT (QT,0) defined by a nonnegative, nondecreasing function T(r) on 0≤r<∞.